2020
DOI: 10.1111/aos.14449
|View full text |Cite
|
Sign up to set email alerts
|

Monocular and binocular end‐points after epiretinal membrane surgery and their correlation to patient‐reported outcomes

Abstract: This study evaluates current available endpoints for epiretinal membrane (ERM) surgery and examine their correlation to patient reported outcomes (PRO). Methods: Retrospective study including 38 eyes of 38 patients who underwent cataract extraction and subsequent vitrectomy for idiopathic ERM. The fellow eye was phakic with good visual acuity. The registered outcomes were monocular and binocular visual acuity, stereoacuity, M-chart metamorphopsia score, aniseikonia and aniseikonia tolerance range (ATR). Two qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The presence of metamorphopsia as well as decreased visual acuity in ERM patients, negatively affects the visual quality. [19] Kim et al, in their study, in which they included 84 patients with stage 2, 3, and 4 ERM, observed a decrease in visual acuity and an increase in metamorphopsia scores as the ERM stage increased in the preoperative period. [13] They reported that EIFL thickness was correlated with metamorphopsia scores in the preoperative period.…”
Section: Discussionmentioning
confidence: 93%
“…The presence of metamorphopsia as well as decreased visual acuity in ERM patients, negatively affects the visual quality. [19] Kim et al, in their study, in which they included 84 patients with stage 2, 3, and 4 ERM, observed a decrease in visual acuity and an increase in metamorphopsia scores as the ERM stage increased in the preoperative period. [13] They reported that EIFL thickness was correlated with metamorphopsia scores in the preoperative period.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, studies on MH and branch retinal vein occlusion patients, along with additional research on ERM surgeries, did not find a significant correlation between metamorphopsia severity and stereoacuity. 17,29,32 The stereotests employed in these studies primarily focused on near vision, lacking assessments for distance stereopsis. Our research contributes quantitative evidence supporting the correlation between metamorphopsia and stereopsis impairment across both near and distance vision, indicating that metamorphopsia significantly impacts the ability for depth perception.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ERM, not only visual acuity but also functional parameters other than visual acuity including metamorphopsia and aniseikonia are important in terms of quality of vision [17][18][19]. A retrospective study including 60 eyes with stage 3 and 4 ERM observed a significant correlation between EIFL thickness and M-score, suggesting that EIFL might be a good indicator of metamorphopsia [16].…”
Section: Discussionmentioning
confidence: 99%